Correlation and regression analysis of the investment attractiveness of the petroleum refining industry - M. M. Gayfullina; G. Z. Nizamova (Управление)
The article presents the results of the analysis of the investment attractiveness of the petroleum refining industry using correlation and regression methods. It has been suggested to evaluate the level of investment attractiveness of the petroleum refining industry through capital productivity. A system of indicators affecting the investment attractiveness of the petroleum refining has been formed in the context of resource and production, financial, economic and social groups of factors. This methodology of correlation and regression analysis for modeling factors affecting investment attractiveness has been presented. The methodology includes the construction of a pair correlation, the selection of factors, the construction of a generalised correlation matrix using the “Correlation” tool in the “Data Analysis” package Microsoft Excel, the regression analysis based on the finally selected factors, the construction of the regression equation, the justification of the obtained dependence using the “Regression” tool in the “Data Analysis” package MS Excel.According to the results of calculations for the type of economic activity “Production of coke and petroleum products” in the Russian Federation in dynamics for 2012 –2019, a strong correlation has been revealed between the output-capital ratio and such factors as the oil refining depth, profit from sales and labor productivity.The results of the study can be used to identify significant factors affecting the investment attractiveness of the petroleum refining industry in order to further optimise them.